PERAN BUDAYA DALAM PENDIDIKAN ILMU PENGETAHUAN SOSIAL - Purba, Serina Defani; Darliana, Eka (Prodi Pendidikan IPS STKIP AL MAKSUM, 2025)
This Article Discusses The Role Of Culture In Social Science Education As An Important Element In Character Building, Social Understanding And Student Identity. Culture Serves As A Medium To Introduce Students To The Values, Norms, Traditions And Diversity Of Society, So That They Can Understand Social Dynamics More Deeply. Through Culture-Based Education, Students Not Only Learn About Social Concepts, But Also Develop Attitudes Of Tolerance, Empathy And Respect For Differences. This Research Uses A Qualitative Approach With A Case Study Method In A School That Integrates Culture In The Social Science Curriculum. Data Were Collected Through In-Depth Interviews, Observation, And Document Analysis, Then Analyzed Thematically. The Results Show That Cultural Integration In Learning Is Able To Improve Students’ Understanding Of Local And Global Social Contexts, Strengthen National Identity, And Prepare Them To Become Broad-Minded Citizens. This Article Emphasizes The Importance Of Culture As An Integral Part Of Social Science Education To Create Relevant, Contextual And Meaningful Learning. It Is Hoped That The Findings Can Serve As A Reference For Educators And Policy Makers In Developing Culture-Based Education.